If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(9 + d) + -9 = 0 (9 * 5 + d * 5) + -9 = 0 (45 + 5d) + -9 = 0 Reorder the terms: 45 + -9 + 5d = 0 Combine like terms: 45 + -9 = 36 36 + 5d = 0 Solving 36 + 5d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 5d = 0 + -36 Combine like terms: 36 + -36 = 0 0 + 5d = 0 + -36 5d = 0 + -36 Combine like terms: 0 + -36 = -36 5d = -36 Divide each side by '5'. d = -7.2 Simplifying d = -7.2
| 375+12x=639 | | 3h+f=8 | | -(p+4)=2 | | f(x)=12x+7 | | 35-2x+3=2x+12+x | | -7(x+7)+234=11+27 | | 4n-4n=-10+1-5n+2n | | 1.54-1/10x | | 2x=-3y+1 | | C/2= | | 9+3y-1y=14 | | 14+23=65 | | -3.5*-5y=-10.1 | | 3-2(-4)=7 | | (N-2)= | | 2x-4/5= | | 3x-18+8=5x-6 | | -8-v=v-1-7 | | 18x4/9 | | 3-2(5)=7 | | 31-2z=43 | | 3v+w= | | (3m+13)+(4m+14)= | | 34-x=-12 | | 3-2(-5)=7 | | 21+26x=28+19x | | 5(y+1)=4(3y+4) | | y=2mx-5 | | 5+(2x+3x)=25 | | 2(13-p)= | | -3(k-8)=24-3k | | 3-3n=7(n-1) |